2007
DOI: 10.1002/chin.200704197
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Relationships Between Type I and Type II Iterative Polyketide Synthases: The Aspergillus parasiticus Norsolorinic Acid Synthase.

Abstract: Iterative Polyketide Synthases: The Aspergillus parasiticus Norsolorinic Acid Synthase. -(MA, Y.; SMITH, L. H.; COX*, R. J.; BELTRAN-ALVAREZ, P.; ARTHUR, C. J.; SIMPSON FRS, T. J.; ChemBioChem 7 (2006) 12, 1951-1958; Sch. Chem., Univ. Bristol, Cantock's Close, Bristol BS8 1TS, UK; Eng.) -Lindner 04-197

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
6
0

Year Published

2007
2007
2008
2008

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 1 publication
2
6
0
Order By: Relevance
“…2A. The ACP domain of PKS13 was verified to be holo and was likely phosphopantetheinylated by the E. coli holo-ACP synthase, as reported for other nonreducing fungal PKS ACP domains (4,16). To assay PKS13 activities, we supplied the purified enzyme with malonyl-CoA as the extender unit and 11-hydroxyundecanyl-S-acetylcysteamine 5 as the starter unit.…”
Section: Resultsmentioning
confidence: 82%
“…2A. The ACP domain of PKS13 was verified to be holo and was likely phosphopantetheinylated by the E. coli holo-ACP synthase, as reported for other nonreducing fungal PKS ACP domains (4,16). To assay PKS13 activities, we supplied the purified enzyme with malonyl-CoA as the extender unit and 11-hydroxyundecanyl-S-acetylcysteamine 5 as the starter unit.…”
Section: Resultsmentioning
confidence: 82%
“…Reconstitution of the catalytic domains as individual enzymes has been successful in analyzing the biochemical and structural features of animal FAS [13] and bacterial type I PKS, including the KS-AT [14,15], KR [16], ACP [17], and thioesterase domains [18][19][20] the UWA algorithm to clone and identify the function of the starter unit:ACP transacylase domain from norsolorinic acid synthase (NSAS) involved in aflatoxin biosynthesis [22]. Recently, Ma et al [23] demonstrated that the standalone NSAS ACP domain can function as the ACP component of a bacterial minimal PKS in vitro.…”
Section: Domains [3]mentioning
confidence: 99%
“…1 A). These domains include the starter-unit:ACP acyltransferase (SAT) involved in starter unit selection (9), KS, malonyl-CoA:ACP transferase (MAT) for extender unit loading (10), product-template (PT) (11), ACP, and thioesterase/claisen-cyclase (TE/CLC) (12). The juxtaposition of these domains enables the megasynthase to initiate, extend, and cyclize the polyketide backbone into multicyclic, fungal-specific products (8).…”
mentioning
confidence: 99%
“…We have recently demonstrated that full-length fungal megasynthases can be expressed and reconstituted in E. coli, hence making this family an attractive machinery for E. coli-based biosynthesis of bacterial aromatic polyketides (13). However, despite the analogous iterative Claisen-like condensations catalyzed by two families of PKSs during chain elongation (10), cyclization modes of the poly-␤-ketone backbones are drastically different (14,15) (Fig. 1).…”
mentioning
confidence: 99%